Cardiac manifestations in patients with classical or cardiac subtype of Fabry disease. Issue 9 (2nd July 2020) - Wang, Wei-Ting; Sung, Shih-Hsien; Liao, Jo-Nan; Hsu, Ting-Rong; Niu, Dau-Ming; Yu, Wen-Chung
Abstract : Background: Fabry disease (FD) is an X-linked lysosomal storage disorder engendered by a deficiency of the enzyme α-galactosidase A, leading to systemic accumulation of glycolipids. Studies have reported that the cardiac subtype of FD has a later onset and minimal extracardiac involvement. However, whether the severity of cardiac involvement differs between the classic and cardiac subtypes of FD remains unclear. Methods: We enrolled consecutive patients with classic FD (n = 22; median age [25th–75th percentile], 47.0 [32.75–56.25] years; men, 72.7%) as well as age- and sex-matched patients with a later-onset cardiac subtype of FD who were selected from our cohort of patients with IVS4 919G>A mutation. FD was diagnosed on the basis of clinical symptoms/signs and pedigree screening of index case, plasma α-galactosidase activity, and molecular analysis. Data on clinical manifestations, laboratory findings, and echocardiogram findings were collected before enzyme replacement treatment. Disease severity was evaluated using the Mainz Severity Score Index score. Results: All female patients demonstrated heterozygous mutations, with five, one, and four of them showing normal α-galactosidase activity, classic FD, and cardiac subtype of FD, respectively. The distributions of left ventricular performance indices and comorbidities, including hypertension, diabetes mellitus, and dyslipidemia, were similar between the two groups. Moreover, MSSI cardiovascular scores did not differ significantly between the groups (classic vs cardiac subtype, 10.0 [2.0–12.5] vs 10.5 [9.0–15.25]; p = 0.277). Conclusion: Cardiac manifestations are similar between patients with classic and cardiac subtype of FD.